Ecophysiological aspects of seed germination in Sagittaria montevidensis biotypes resistant and susceptible to herbicides - Pitol, Andressa (2022)
The objective of this work was to evaluate the ecophysiological aspects of seed germination in California arrowhead (Sagittaria montevidensis) biotypes resistant and susceptible to herbicides. The experimental design was completely randomized. In paddy rice fields, seeds were collected from two biotypes that are resistant (SAGMO 10 and SAGMO 32) and from one that is susceptible (SAGMO 35) to acetolactate synthase and photosystem II inhibiting herbicides. Seed dormancy release was performed with 2.0% potassium nitrate, chemical (1.0% H2SO4 for 30 s) and mechanical (sandpaper) scarification, 10 ppm gibberellic acid, water imbibition for 24 hours, water bath at 60°C, and a control. Germination was evaluated at temperatures from 10 to 40°C and seedling emergence at 0.0, 0.5, 1.0, 2.0, 4.0, and 5.0 cm burial depths. All biotypes showed a germination higher than 70% after mechanical scarification. The highest germination rate occurs at 25.9°C for SAGMO 35, the susceptible biotype, and at 26.2 and 26.5°C, respectively, for SAGMO 10 and SAGMO 32, the resistant biotypes. For all biotypes, the highest seedling emergence occurs in seeds positioned at the 0.5 and 1.0 cm burial depths.